Assessment of benthic macroinvertebrates at Nile tilapia production using artificial substrate samplers - M. S. G. Moura e Silva; T. S. Graciano; M. E. Losekann; A. J. B. Luiz (Brazilian Journal of Biology)
Abstract Biomonitoring is a cheap and effective tool for evaluation of water quality, and infer on the balance of aquatic ecosystems. The benthic macroinvertebrates are bioindicators sensitive to environmental changes, and can assist in detecting and preventing impacts such as organic enrichment and imbalance in the food chain. We compared the structure of benthic communities on artificial substrate samplers located in places near and far from net cages for production of Nile tilapia (Oreochromis niloticus). Samplers were manufactured with nylon net, using substrates such as crushed stone, gravel, loofah and cattail leaves. Samples were collected after 30 days of colonization, rinsed and then the specimens were identified and quantified. The following metrics were calculated: richness of Operational Taxonomic Units, Margalef richness, abundance of individuals, Shannon index and evenness index. The macrobenthic community structure was strongly modified according to the proximity of the net cages. Metrics showed significant differences (p < 0.05) between near and distant sites, for both periods (dry and rainy seasons). The position of the samplers significantly affected the structure of macroinvertebrate community, as near sites showed higher values for the community metrics, such as richness and diversity. Near sites presented a larger number of individuals, observed both in the dry and rainy seasons, with a predominance of Chironomidae (Diptera) in the dry season and Tubificidae (Oligochaeta) in the rainy season.